Comprehensive Management of Premature Skin Aging: Current Strategies, Treatments, and Emerging Therapies - Ziobro, Anna; Camlet, Katarzyna; Kocur, Kinga; Lis, Paulina (Journal of Education, Health and Sport, 2024)
Introduction and Aim. Premature skin aging results from both intrinsic and extrinsic factors, requiring a comprehensive management strategy. This review evaluates current and emerging approaches for preventing and treating premature skin aging, focusing on efficacy and safety. Materials and Methods. A review of recent scientific literature on topical, oral, and procedural interventions for managing premature skin aging was conducted. Analysis of Literature. Topical treatments, particularly retinoids and antioxidants, are key in skin regeneration and oxidative stress reduction. Oral interventions, including systemic retinoids and nutraceuticals, support overall skin health. Procedural methods like laser therapies, microneedling, and chemical peels are effective in skin rejuvenation. Preventive measures, such as photoprotection and lifestyle changes, are crucial. Emerging therapies, such as stem cell treatments, show promise in reversing age-related skin changes. Conclusion. Managing premature skin aging requires a combination of topical, oral, and procedural treatments with preventive strategies. Future research should focus on refining protocols, assessing novel therapies’ long-term safety, and developing personalized approaches considering genetic, environmental, and lifestyle factors.